Planning For The Development Of Technical Competence In Land Management (Case Study At The Regional Office Of The National Land Agency, DKI Jakarta Province) - Dyah Ayu Puspitaningtyas; Asrofi Asrofi; Hamka Hamka (Green Publisher Indonesia, 2024)
This study aims to design a development plan for technical competencies in land management, specifically within the Regional Office of the National Land Agency (BPN) DKI Jakarta Province. The complexity of land issues in urban areas like Jakarta necessitates the improvement of technical competencies among functional land administrators to ensure effective performance and service delivery. Using a qualitative research approach, data was gathered through interviews, observations, and document analysis. The research highlights the absence of a structured competency development plan for land administrators and suggests the need for tailored training programs. Findings emphasize the importance of digital literacy, land administration skills, legal expertise, and communication skills to meet the demands of modern land management. The study concludes with recommendations for competency development that aligns with organizational goals, proposing a competency framework tailored to the challenges faced in Jakarta.